2017
DOI: 10.1080/13557858.2017.1373072
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and reality: perceptions of support among African American breast cancer survivors

Abstract: Applying transitions theory, we found that social support is a process of bidirectional negotiation where African American women with breast cancer perceive support as helpful and acceptable depending on who offers support, what type of support is offered, and when it is offered. Members of their social support network (e.g. family, friends, providers) should periodically assess the survivor's evolving needs to ensure the social support harmonizes with the needs and expectations of the survivor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Emotional support was particularly important to some participants [58,59]. In one study, participants identified support as helpful only when it was in line with what they expected/desired [60]. Many survivors appreciated the impact of survivorto-survivor relationships [59,[61][62][63].…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional support was particularly important to some participants [58,59]. In one study, participants identified support as helpful only when it was in line with what they expected/desired [60]. Many survivors appreciated the impact of survivorto-survivor relationships [59,[61][62][63].…”
Section: Social Supportmentioning
confidence: 99%
“…In terms of sources of support, some survivors expressed a desire for family members to support the healthcare provider's plan and/or provide instrumental support such as driving to treatment [60]. Others mentioned their relationship with healthcare providers positively influencing their emotional health [61] and believed it was part of providers' jobs to…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this concurrent convergent mixed methods study [28] was to provide further data to guide the development of the proposed culturally sensitive mHealth app, STORY+ for African-American women with breast cancer. Our initial work has been reported [14,[29][30][31][32][33][34]. The aims of this study were to (1) assess the use of smartphones and computers related to health care in African-American women with breast cancer, and (2) identify foundational aspects to support endocrine therapy adherence for incorporation in an mHealth app.…”
Section: Introductionmentioning
confidence: 99%
“…African American women with breast cancer are at a higher risk for diminished health and emotional support information for survivorship from healthcare providers [ 7 ] and negative responses from family and friends. A social connectedness to others is an important aspect of survivorship for African American women with breast cancer, and yet, many of these women encounter feelings of social isolation within their networks of family and friends who may not understand the psychosocial issues encountered during post-treatment [ 13 ]. These challenges were likely heightened for African American women with breast cancer during the COVID pandemic.…”
mentioning
confidence: 99%